Pengaruh Strategi Digital Marketing Tiktok Terhadap Peningkatan Penjualan Produk Yamara Fashion - Santosa, Fadila Adelia Putri; Janah, Nurul; Mentari, Laisa Nurin (LPPM STT Terpadu Nurul Fikri, 2025)
TikTok has emerged as a dominant platform in digital marketing strategies, driven by its engaging short-form video content and algorithmic distribution tailored to user preferences. In Indonesia, TikTok reached 157.6 million users by July 2024, establishing itself as the fastest-growing social media platform in Southeast Asia and offering high potential for enhancing product visibility and sales, particularly for fashion businesses. Toko Yamara, a local enterprise specializing in fashion since 2020, actively utilizes TikTok for marketing; however, sales fluctuations observed from April to August 2024 highlight inconsistencies in its marketing approach. This study examines the impact of TikTok-based digital marketing strategies on sales performance at Toko Yamara, focusing on four key dimensions: accessibility, interactivity, entertainment, and informativeness, alongside engagement metrics—including likes, comments, shares, and saves—that reflect audience interaction. Employing an explanatory quantitative approach, the research involved 116 consumers exposed to Toko Yamara’s TikTok content, selected through purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed through validity and reliability tests, simple linear regression, t-tests, and coefficient of determination. Results indicate a statistically significant influence of TikTok digital marketing on sales growth, with a coefficient of determination (R²) of 49.6%. These findings underscore the importance of optimizing informative and engaging content for small businesses to strengthen social media-based marketing efforts and provide empirical backing for consumer purchase decisions.